Light at Home survey - Maini Gerhardsson, Kiran (Lund University, 2019)
Aim: To investigate the current lighting situation in Swedish homes with regard to lamp purchasing behaviour, lighting characteristics and light related behaviour.
Primary research question: What lighting do Swedish residents have in their homes and what are the factors influencing their illumination choices?
subsidiary research questions: Which lamps do residents buy, where are they placed and how are they controlled?
Do residents have the lighting they want, and which key factors influence their choices?
Method and sampling strategy: A random sample of 2000 residents drawn by the Swedish Address Registry (SPAR) resulted in 536 responses,18–80 yr.
Data collection: Nov 2015.

Purpose:

The aim of the survey “Light at Home” was to investigate the current lighting situation in Swedish homes with regard to lamp purchasing behaviour, lighting characteristics and light related behaviour.

A paper-and-pencil questionnaire was sent to a random sample of 2000 people which was drawn by the Statens personadressregister (SPAR) from the adult (18–80 yr) population of Lund, a city located in the south of Sweden. The number of returned paper-and-pencil questionnaires after one reminder was 536 (female 51% and male 49%).

Syftet med studien "Ljuset hemma" var att undersöka den befintliga ljussituationen i svenska hem genom kvantitativa metoder. En enkät skickades ut till ett slumpmässigt urval med 2000 boende mellan 18 och 80 år i Lunds kommun.

Syfte:

Syftet med studien "Ljuset hemma" var att undersöka den befintliga ljussituationen i svenska hem med avseende på inköp och placering av olika ljuskällor, vad som karaktäriserar belysningen och ljusrelaterat beteende i hemmet.

Ett frågeformulär skickades till ett slumpmässigt urval som drogs av (SPAR) från den vuxna befolkningen (18-80 år) i Lund. Efter en påminnelse blev antalet returnerade svar 536 (kvinnor 51% och män 49%).
Ljuset hemma
Keywords: lighting; belysning; Housing; Bostäder; Behavior; Beteende; Social Sciences; Samhällsvetenskap